Filling gaps on seed germination and species selection in drylands of Argentina: Work in progress and reflections on intelligent tinkering - Rodriguez Araujo, Maria Emilia; Pérez, Daniel; Aronson, James; Cross, Adam (Consejo Nacional de Investigaciones Científicas y Técnicas, 2021)
Ecological restoration and rehabilitation (ERR) practitioners lack comprehensive information on the most effective seed dormancy alleviation treatments to enhance germination of native plants from arid and semiarid regions, as well as on survival and growth rates of these species in the field. In this paper we report on the results of a “professional intelligent tinkering” approach to assess seed germination of species from the Monte Austral, an arid region in southern Argentina. We aim to test a small number of seed dormancy alleviation treatments reported to be effective in other arid regions, and to assess germination results for 16 species against existing information on their performance in the field. This approach proved to be highly effective given that, out of the 16 shrub species evaluated, 11 showed germination rates suitable for ERR (i.e., over 50%). Only four species attained both high survival rates and plant cover values in outplantings, while four other species showed high survival rates but their plant cover values were low or not assessed. We argue that this approach, which involves obtaining and comparing data on seed germination rate with performance of the same species in the field, would be strategic for species selection in ERR.